Rewiring your preaching how the brain processes sermons - Cox, Richard H. (Downers Grove, Illinois : IVP Books, 2012)
Psychologist, physician and preacher Richard Cox shows that better understanding of the brain can help preachers be more effective in their preaching. God is at work in our brains to enable his people to hear him. Preach with the brain in mind, and help your hearers grow in mental, physical and spiritual health. --from publisher description.
A brainstorm versus a short circuit -- Linking brain and sermon -- The brain sees preaching as unique -- The brain uses preaching for healing -- The core process of preaching is brain work -- Preaching provides brain energy -- Brain stimuli produce behavioral responses -- Preaching and pastoring are different -- Getting to the brain with theology -- Preaching and the brain in pain -- Brain healing and the soul -- Brain healing and the mind -- Brain healing and the body -- Brain healing and the community -- Dénouement and benediction.
Includes bibliographical references.
Description based on print version record.
Keywords: Preaching; Brain -- Religious aspects -- Christianity; Thought and thinking -- Religious aspects -- Christianity; Psychology, Religious; RELIGION / Christian Ministry / Preaching; Electronic books